The Deep Learning Approach to Pedagogical Knowledge in Pancasila Learning: A Study of Prospective Elementary School Teachers - Yunita Rahma Pratiwi, Emy Yunita Rahma Pratiwi; Dwinata, Anggara; Masitah Ahmad (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study investigates the application of deep learning in Pancasila education lessons for prospective elementary school teachers during microteaching. The deep learning approach in Pancasila learning emphasizes three main principles: mindfulness, joyfulness, and meaningfulness. Method: This qualitative research employed an exploratory design, using questionnaires and interviews for data collection. Results: The questionnaire responses from prospective elementary school teachers yielded an average score of 87.33%. Interview findings revealed that the deep learning approach in Pancasila learning significantly enhances the pedagogical knowledge of prospective elementary school teachers. Novelty: This approach introduces an innovative method for teaching Pancasila at the elementary level, emphasizing the teacher’s role in fostering mindful, joyful, and meaningful learning experiences. Future Studies: The deep learning approach should be applied not only in Pancasila learning but also in other subjects, with adaptations to specific learning components to maximize educational outcomes.